Eksistensi Dan Regenerasi Komunal Tari Baris Gede di Desa Adat Umeanyar - I Putu Merta; Ida Bagus Wika Krishna; I Nyoman Raka (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
This research is motivated by the imbalance in the condition of the Baris Gede Dance at the Puseh Temple in Umeanyar Traditional Village. The physical preservation of the dance remains intact, but there is a weakening in the transmission of values ​​and fragmentation of symbolic meaning among the younger generation due to the process of modernization. The research aims to analyze the relationship between performative practices, symbolic structures, and the dynamics of regeneration challenges, and to formulate a model for cultural preservation at the local level. This study analyzes the relationship between performative practices, symbolic structures, the dynamics of regeneration challenges, and to formulate a model for cultural preservation at the local level. The research method used is qualitative with a case study design and an interpretive ethnographic approach, utilizing participant observation, in-depth interviews, and analysis of traditional documents. The results reveal three main findings: first, the formal physical continuity of the dance is very strong due to the support of customary regulations and collective obligations of ngayah; second, there are serious challenges to communal regeneration in the form of time desynchronization due to work mobility, incidental training, and the shallow internalization of the philosophical meaning of movements (nyongkok, matayungan) and local nomenclature. Third, an operational community-based preservation strategy (community-based safeguarding) is needed through the design of a structured training curriculum integrated with digital video tutorials, strengthening customary decisions (perarem), allocating special funding (dana dresta), and aesthetic control over modern cosmetics. In conclusion, the existence of sacred art is not solely measured by the frequency of physical performances, but rather by the effectiveness of the transmission of cultural and spiritual knowledge that adapts to the realities of modern youth in order to maintain the dance's taksu (spiritual power).